Various genetic types of end moraines in the city of Poznań and its close vicinity, central-western Poland - Widera, Marek; Chomiak, Lilianna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The current research focuses on explaining the origin of end moraines running through the northernmost districts of the city of Poznań. The highest hills, that is, the Moraska Hill and the Dziewicza Hill, are a stagnation record of the Vistulian Glaciation of the Poznań Phase. These two hills represent terminal moraines of similar height and age, but the mechanism of their formation is diametrically opposed.
Keywords: Pleistocene of central-western Poland; accumulative moraines; push end moraines; depositional processes; deformational processes; Scandinavian ice sheet; Plejstocen; Polska środkowo-zachodnia; moreny akumulacyjne; moreny pchające; procesy depozytowe; procesy deformacyjne; skandynawskie pokrywy lodowe; lodowiec skandynawski